Defining an optimal stromal derived factor‐1 presentation for effective recruitment of mesenchymal stem cells in 3D. Issue 11 (14th July 2014) - Iannone, Maria; Ventre, Maurizio; Pagano, Gemma; Giannoni, Paolo; Quarto, Rodolfo; Netti, Paolo Antonio
ABSTRACT In "situ" tissue engineering is a promising approach in regenerative medicine, envisaging to potentiate the physiological tissue repair processes by recruiting the host's own cellular progenitors at the lesion site by means of bioactive materials. Despite numerous works focused the attention in characterizing novel chemoattractant molecules, only few studied the optimal way to present signal in the microenvironment, in order to recruit cells more effectively. In this work, we have analyzed the effects of gradients of stromal derived factor‐1 (SDF‐1) on the migratory behavior of human mesenchymal stem cells (MSCs). We have characterized the expression of the chemokine‐associated receptor, CXCR4, using cytofluorimetric and real‐time PCR analyses. Gradients of SDF‐1 were created in 3D collagen gels in a chemotaxis chamber. Migration parameters were evaluated using different chemoattractant concentrations. Our results show that cell motion is strongly affected by the spatio‐temporal features of SDF‐1 gradients. In particular, we demonstrated that the presence of SDF‐1 not only influences cell motility but alters the cell state in terms of SDF‐1 receptor expression and productions, thus modifying the way cells perceive the signal itself. Our observations highlight the importance of a correct stimulation of MSCs by means of SDF‐1 in order to implement on effective cell recruitment. Our results could be useful for the creation of a "cell instructive material" that is capable to communicate with the cells and control and direct tissue regeneration. Biotechnol. Bioeng. 2014;111: 2303–2316. © 2014 Wiley Periodicals, Inc.